Estudio de prefactibilidad para la instalación de un centro ecoeficiente de fisioterapia dirigido al adulto mayor en la ciudad de Lima - Castillo Salazar, Juan Carlos Cris (2015)
The main aim of the present research project is to demonstrate the technical, economic and market feasibility of implementing an establishment that provides physiotherapy services for seniors of the city of Metropolitan Lima focused on improving the quality of life for patients, increasing the level of service of its therapies and optimizing the efficiency of its facilities through the implementation of an environmental management system based on the eco-efficiency which will contribute to sustainable development and mitigation of the environmental impact in the project´s area of influence.